2014
DOI: 10.3109/2000656x.2014.988218
|View full text |Cite
|
Sign up to set email alerts
|

Double innervated free functional muscle transfer for facial reanimation

Abstract: The double innervated gracilis muscle flap is a viable technique for the treatment of long-standing facial palsy. It enables a fast recovery with fast muscle activity, and allows an emotional smile and aesthetic symmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 27 publications
1
68
0
3
Order By: Relevance
“…17 Another challenge in facial reanimation surgery is a current standard on how to consistently report the restoration of facial movement and symmetry. For example, Hontanilla et al recently reported better symmetry in gracilis muscles powered by the showing excellent/good outcomes on the majority of patients based on the Terzis functional and aesthetic grading system 11,19 secondary procedures are also commonly performed to address late facial movement inadequacies or facial asymmetries by augmenting the functional muscle transfer. While authors have reported their techniques for augmentation, it remains unclear as to the actual incidence or rate that is necessary for these secondary procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Another challenge in facial reanimation surgery is a current standard on how to consistently report the restoration of facial movement and symmetry. For example, Hontanilla et al recently reported better symmetry in gracilis muscles powered by the showing excellent/good outcomes on the majority of patients based on the Terzis functional and aesthetic grading system 11,19 secondary procedures are also commonly performed to address late facial movement inadequacies or facial asymmetries by augmenting the functional muscle transfer. While authors have reported their techniques for augmentation, it remains unclear as to the actual incidence or rate that is necessary for these secondary procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Multiple published articles on gracilis free muscle transfer for facial reanimation have detailed patient outcomes, various surgical techniques, rehabilitative measures following surgery, and available alternative options within the procedure such as the choice of donor motor nerve. [9][10][11][12] Despite the expanding literature on facial reanimation with the gracilis muscle, less has been reported on its associated early complications. To our knowledge, only two articles (reported by the same authors at the same institution) have specifically been written to detail and highlight the early complications (infection rates) following gracilis free muscle transfer for facial reanimation.…”
mentioning
confidence: 99%
“…To minimize morbidity, it may be possible to collect subcritical muscle biopsies from contralateral muscle sources. Ultimately, the use of a MM grafting may have the greatest utility for the repair of smaller muscles like those of the face 31 and hands 32 where a therapeutic volume of MM muscle could be harvested from the larger muscle of the lower limbs in a manner consistent with the harvest or the middle third of the patellar tendon during anterior cruciate ligament reconstruction. 33 The encouraging signs of functional regeneration that were observed in response to MM implantation hint at additional cellular implantation factors that may enhance myogenesis within DSM implants.…”
Section: Decellularized Skeletal Muscle With Minced Muscle Autograftsmentioning
confidence: 99%
“…However, questions related to surgical treatment of facial paralysis have led to double muscle innervation hypothesis 8 . Therefore, to enlighten this issue, two different motor units experimental model become interesting, making the study of the tibial and fibular branches of the sciatic nerve relevant.…”
Section: Introductionmentioning
confidence: 99%